Interview of George A. Doumani by Brian Shoemaker - Doumani, George A. (Byrd Polar Research Center Archival Program, 2005)
George Toney, pp. 3, 12, 23 Bill Chapman, pp. 3, 5, 21, 26 Sir Hubert Wilkins, pp. 14, 16 Charles White, pp. 15 George Dufek, pp. 16-17 Admiral Tyree, pp. 16-17, 43 Harry Wexler, pp. 17 Tom Jones, pp. 18 Bert Crary, pp. 18-19, 58, 60, 71 Ned Ostenso, pp. 18 Charlie Bentley, pp. 19, 22, 26, 36 Hal Borns, pp.20 Joe Walker, pp. 23 Emil Shophless, pp. 25 Bill Long, pp. 25-26, 32-33, 41-47, 49 Fred Darling, pp. 25-26 Jock Pirritt, pp. 26-27, 30, 33, 36 Hugh Audeshaw, pp. 29 Edward Galla, pp. 31 Frank Chang, pp. 32, 36 _______Born, pp. 39 Dick Cameron, pp. 41-42, 58-59 Dick Goldthwaite, pp. 41 Colin Bull, pp. 41 Jim Schopf, pp. 44, 46 _______Skinner, pp. 46, 56 Larry Lackey, pp. 46 Tex Minchew, pp. 46 Admiral Reedy, pp. 46-47, 49-50, 64 Captain Frank Radspinner, pp. 52-53 Captain Early, pp. 53, 57 Dee DiAngelo, pp. 53-57 Art Boucot, pp. 59-61, 63 Sir Grand de la Comb, pp. 65 John Spletz, pp. 70 Fritz Hollings, pp. 71, 73 Ray Hunt, pp. 75 President George Bush, pp. 75 Admiral Watkins, pp. 76 _______Peterson, pp. 76 The media can be accessed at the links below. Audio Part 1: http://streaming.osu.edu/knowledgebank/byrd/oral_history/George_Doumani_1.mp3 Audio Part 2: http://streaming.osu.edu/knowledgebank/byrd/oral_history/George_Doumani_2.mp3 Dr. Doumani received his Bachelor’s Degree in Geological Sciences from the University of California Berkeley, with a concentration on energy. He continued at Berkeley, receiving his Master’s Degree in Estratographic Paleontology. After finishing his graduate work, Dr. Doumani went on to work as an engineer and eventually found an ad in Geotimes Magazine for a position to do Antarctic work. He was hired as a geophysicist near the end of IGY (International Geophysical Year, 1957-58) and began his training in Washington, D.C. at the National Science Foundation and the Rand Corporation (to study the gyrocompass). The trip to McMurdo Station took 42 hours from Washington, D.C. Dr. Doumani recalls his interactions with several notable Antarctic explorers including Sir Hubert ...